Entering Into the Story: Implications for Emergent Literacy - Sperry, Linda L.; Sperry, Douglas E. (Frontiers in Psychology, 2021)
In this article we explore the ways in which three young African American children from the Rural South create stories with the assistance of their caregivers and siblings in the social contexts of their homes. We assert that these children’s oral narrations show us important dimensions of early experience with decontextualized content that may offer suggestions for culturally sensitive experiences with conventional literacy. The dimensions we highlight are the tangibility of the elements around which the story is created, the interlocutor support children receive for beginning and continuing their stories, and the interaction between the storytelling process and the child’s self-interest. These three dimensions illustrate how children “enter” into stories and storytelling and provide the foundation for fostering culturally sustaining pedagogy within schools.